Are landscape approaches possible under authoritarianism? multi-stakeholder governance and social transformation in Myanmar - Forsyth,T.; Springate-Baginski, O. (Elsevier, 2021)
Landscape Approaches have been proposed as a transferable model of multi-stakeholder governance, yet assume conditions of ideal speech, trust, and transparency that seem untransferable to authoritarian regimes. This paper argues that building Landscape Approaches under authoritarian conditions cannot be based on a governance deficit model of awaiting idealized political conditions, but instead needs to pay attention to how local social and political structures influence what is deliberated, and by whom. The paper presents evidence from a multi stakeholder environmental intervention around Lake Indawgyi in Kachin State, Myanmar, to draw lessons for transferring Landscapes Approaches under conditions of political authoritarianism, sporadic violent conflict, and rapid socio-economic change. Using information gathered from village surveys and interviews with policy makers, the paper analyzes how multifunctionality, stakeholder engagement, and deliberation are achieved, and with whose influence. The paper argues that common principles of Landscapes Approaches need to acknowledge more how state-led agendas can influence agendas and participation in conservation; but also how the composition and interests of stakeholders are not fixed under socio-economic transformation. Focusing on local and contextual drivers of environmental change and political inequality are more useful for transferring Land scape Approaches to authoritarian regimes than adhering to optimistic principles, or testing associations between variables without reference to context. Indeed, the latter risks depoliticizing conflictual processes, and implicitly endorsing political inequalities. The 2021 military coup in Myanmar has added to these inequalities.